Temperature-resistant gel foam system based on polymer surfactant and application

By using a temperature-resistant frozen glue foam system based on surface polyester in heavy oil reservoirs, the problem of poor water control ability of traditional profiling technology in high temperature environments is solved, and the high stability and long-term effect of the foam is achieved, improving the The development efficiency of heavy oil reservoirs is achieved.

CN119432341AInactive Publication Date: 2025-02-14CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202310979734.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-04
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing profiling process has poor water control capabilities during thermal production of heavy oil reservoirs, which cannot meet production needs, and the traditional water-based foam system is insufficient in high temperature environments.

Method used

Using a temperature-resistant frozen glue foam system based on polyester, the system includes polymer, polyester, crosslinking agent, foaming agent and oxygen deoxidizer. By optimizing the dosage and combination of these ingredients, the stability of the foam is improved and Water control capability.

Benefits of technology

The high stability and long-term effect of the foam are achieved, the water control ability is enhanced in high temperature environments, and the water flow and gas flow are effectively blocked, which improves the development efficiency of heavy oil reservoirs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119432341A_ABST
    Figure CN119432341A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of oil extraction, profile control and plugging of oil reservoirs, in particular to a temperature-resistant gel foam system based on a polymer surfactant and application. The system comprises the following components in percentage by mass: 0.1%-5% of a polymer, 0.15%-0.35% of a poly-surfactant, 0.1%-1.0% of a cross-linking agent, 0.1%-0.6% of a foaming agent, 0.1%-0.5% of a deoxidant and the balance of water. The system is high in foam stability and good in temperature resistance, meanwhile, the gelling time of gel foam is prolonged, the aging rate of the gel foam system in the injection process is increased, and the swept volume of the gel foam system is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oil reservoir oil production profile control and plugging, and in particular to a temperature-resistant jelly foam system based on a polymerizing agent and an application thereof. Background Art

[0002] After years of exploitation, a considerable part of my country's oil reservoirs have entered the stage of tertiary oil recovery. At present, many heavy oil reservoirs in my country are difficult to exploit, and their asphaltene and colloid grade components are high and have high viscosity. Therefore, my country's heavy oil exploitation is often carried out in the form of thermal recovery, mainly including steam drive, steam huff and puff and fire drive. However, with the increase in the degree of exploitation, the reservoir environment has gradually become worse, the formation heterogeneity has increased, and the water and gas channeling phenomena have become prominent during the exploitation process, which has seriously restricted the development efficiency of heavy oil reservoirs. Therefore, it is urgent to adopt effective profile control and water control technology to improve the formation structure and achieve the purpose of water control and efficiency enhancement during heavy oil thermal recovery. The traditional profile control process is often carried out by injecting nitrogen foam into the oil layer. This process can play a certain role in improving the formation heterogeneity, but due to the low strength, short half-life and insufficient thermal stability of the ordinary water-based foam system, the system has a short action time in the formation, and the water control ability is poor, which cannot meet the needs of the production process.

[0003] The gel foam system is a new profile control system that is obtained by strengthening the foam liquid film structure on the basis of the ordinary foam system. Compared with the traditional foam system, it has similar fluidity to the ordinary foam system before gelation and good injectability. Under the high temperature environment of the formation, the high molecular polymers in the system liquid film are gradually cross-linked, so that the liquid film forms a gel wall, thereby strengthening the foam system, which makes the foam system have higher strength and stability.

[0004] CN102604606B provides a secondary cross-linked chemical gel foam plugging liquid, the mass percentage of each component of which is: hydrolyzed polyacrylamide, 0.1-0.35%, non-ionic polyacrylamide, 0.1-0.25%; bisphenol resin cross-linking agent, 0.2-1.2%; chromium lactate cross-linking agent, 0.002-0.006%; sodium nitrite, 0.2-1.1%; ammonium chloride, 0.3-0.8%; oxalic acid, 0.01-0.05%; sodium bentonite, 0.2-0.4%; and the rest is water.

[0005] CN113201318B provides a high temperature and high salt resistant reinforced foam plugging agent, wherein the main agent is lignin, the cross-linking agent is urotropine, the foaming agent is HZ-1 type, and the reinforcing agent is methyl cellulose with a molecular weight of 80,000 to 200,000; in terms of mass percentage, the lignin is 4.0 to 6.0%, the urotropine is 3.5 to 5.5%, the methyl cellulose is 0.3 to 0.6%, the HZ-1 type foaming agent is 0.5%, and the balance is water.

[0006] CN110982502A provides a high temperature resistant gel foam, which comprises the following raw materials: 0.3% to 0.9% of a heat and salt resistant polymer, 0.2% to 0.9% of phenol or hydroquinone, 0.2% to 0.9% of formaldehyde, polyformaldehyde or hexamethylenetetramine, 0.2% to 0.8% of a foaming agent, 0.3% to 0.6% of an organic substance containing a phosphonic acid structure, 0.3% to 0.7% of an auxiliary agent, and the balance is water; wherein the organic substance containing a phosphonic acid structure is one or more of aminomethylphosphonic acid, phenylphosphonic acid, and hexylphosphonic acid;

[0007] Common jelly foam systems mainly use polymers as base liquids, add cross-linking agents and foaming agents, and prepare jelly foams by stirring and foaming. However, it is usually difficult for jelly foam systems to maintain a stable foam shape before the polymers are cross-linked into gels. At the same time, the jelly foam system needs to have good fluidity during the injection process into the formation. Summary of the invention

[0008] The main purpose of the present invention is to provide a temperature-resistant gel foam system based on a surfactant and its preparation method and application. The system of the present invention has strong foam stability and good temperature resistance, while prolonging the gelling time of the gel foam, increasing the aging rate of the gel foam system during the injection process, and increasing its swept volume.

[0009] To achieve the above object, the present invention adopts the following technical solutions:

[0010] The invention provides a temperature-resistant jelly foam system based on a surfactant polymer. The system comprises the following components: by mass percentage, 0.1% to 5% of a polymer, 0.15% to 0.35% of a surfactant polymer, 0.1% to 1.0% of a crosslinking agent, 0.1% to 0.6% of a foaming agent, 0.1% to 0.5% of an oxygen scavenger, and the balance is water.

[0011] The polymer surfactant acts in the system, which not only strengthens the viscosity of the polymer solution and reduces the surface tension of the foam liquid film, but also promotes the emulsification and viscosity reduction process of the heavy oil system to a certain extent, ultimately achieving the purpose of stabilizing the foam and enhancing the heat resistance. At the same time, it prolongs the gelling time of the gel foam, increases the aging rate of the gel foam system during the injection process, and increases its swept volume.

[0012] Furthermore, the crosslinking agent is composed of zirconium acetate and low-activity phenolic resin, in which the mass percentage of zirconium acetate is 0.075%-0.225% and the mass percentage of low-activity phenolic resin is 0.4%-0.8%. The crosslinking agent is recorded as composite crosslinking agent I.

[0013] Furthermore, the crosslinking agent is composed of zirconium acetate and polyethyleneimine, in which the mass percentage of zirconium acetate is 0.075%-0.225% and the mass percentage of polyethyleneimine is 0.05%-0.2%. The crosslinking agent is recorded as compound crosslinking agent II.

[0014] Furthermore, the crosslinking agent is composed of zirconium acetate and high-activity phenolic resin, in which the mass percentage of zirconium acetate is 0.075%-0.225% and the mass percentage of high-activity phenolic resin is 0.6%-1.0%. The crosslinking agent is recorded as composite crosslinking agent III.

[0015] The gelling experiment and the analysis of the stability of the gel foam show that the composite crosslinking agents I, II and III of the present invention have a relatively long foam half-life and high temperature stability.

[0016] Furthermore, the foaming agent is sodium lauryl sulfate.

[0017] The present invention also provides the use of the above-mentioned temperature-resistant gel foam system based on the polymer surface agent in the high-temperature heterogeneous oil layer exploitation process of steam stimulation, wherein the core permeability of the oil layer is 0.247-0.502 μm 2 .

[0018] Compared with the prior art, the present invention has the following advantages:

[0019] The present invention obtains the temperature-resistant gel foam system surfactant by optimizing and screening the components and / or dosages of the crosslinking agent, the foaming agent and the surfactant. The temperature-resistant gel foam system of the present invention is a high-stability gel foam system with good rheological properties and swept volume. The gel foam system of the present invention can form an effective plugging in the core, has a good effect of inhibiting water and gas channeling, and has broad application prospects in high-temperature heterogeneous oil layers with steam intake and discharge. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 After aging at 120℃ for 3 days, the gelling state diagram of the compound system I gelling system;

[0021] Figure 2 The curve of the foaming volume of the foaming agent changing with its mass concentration;

[0022] Figure 3 The curve of foam half-life changing with its mass concentration;

[0023] Figure 4 Comparison of comprehensive foam values ​​before and after high temperature treatment with different foaming agents;

[0024] Figure 5 Changes in the morphology of different compound cross-linked gel foam systems with aging time at 120°C;

[0025] Figure 6 The variation curve of gel foam liquid volume with the content of surfactant;

[0026] Figure 7 The variation curve of foam viscosity of gel foam system with the content of surfactant;

[0027] Figure 8 Curves of viscosity variation with shear time for water-based foam, polymer foam, unaged gel foam and aged gel foam;

[0028] Fig. 9 Curves showing changes in viscosity of unaged and aged jelly foams as a function of shear rate:

[0029] Fig.10 Curves showing changes in viscosity and separation height of gel foam with aging temperature;

[0030] Fig.11 The variation of the precipitate half-life of gel foam with temperature;

[0031] Fig.12 Curve of the amount of precipitated liquid from gel foam changing with NaCl content;

[0032] Fig.13 The viscosity of jelly foam changes with NaCl concentration;

[0033] Fig.14 Optical microscope images of different foams at 100 times magnification: (1) water-based foam, (2) polymer foam, and (3) gel foam;

[0034] Fig.15 1000x scanning electron micrographs of different foams: (1) water-based foam, (2) polymer foam, and (3) gel foam;

[0035] Fig.16 Diagram of the plugging experimental device of the present invention;

[0036] Fig.17 Effect of different matrix permeability on the plugging performance of gel foam. DETAILED DESCRIPTION

[0037] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0038] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations and / or combinations thereof.

[0039] The invention mainly provides a temperature-resistant jelly foam system based on a surfactant polymer, which comprises the following components: by mass percentage, 0.1% to 5% of a polymer, 0.15% to 0.35% of a surfactant polymer, 0.1% to 1.0% of a crosslinking agent, 0.1% to 0.6% of a foaming agent, 0.1% to 0.5% of an oxygen scavenger, and the balance being water.

[0040] As a preferred embodiment of the present invention, the crosslinking agent is composed of zirconium acetate and low-activity phenolic resin, in which the mass percentage of zirconium acetate is 0.075%-0.225% and the mass percentage of low-activity phenolic resin is 0.4%-0.8%. The crosslinking agent is recorded as compound crosslinking agent I.

[0041] As a preferred embodiment of the present invention, the crosslinking agent is composed of zirconium acetate and polyethyleneimine, in which the mass percentage of zirconium acetate is 0.075%-0.225% and the mass percentage of polyethyleneimine is 0.05%-0.2%. The crosslinking agent is recorded as compound crosslinking agent II.

[0042] As a preferred embodiment of the present invention, the cross-linking agent is composed of zirconium acetate and high-activity phenolic resin, in which the mass percentage of zirconium acetate is 0.075%-0.225% and the mass percentage of high-activity phenolic resin is 0.6%-1.0%. The cross-linking agent is recorded as composite cross-linking agent III. As a preferred embodiment of the present invention, the foaming agent is any one of sodium lauryl sulfate, cocamidopropyl betaine, and sodium α-olefin sulfonate.

[0043] As a preferred embodiment of the present invention, the deoxidizer is thiourea.

[0044] As a preferred embodiment of the present invention, the polymer is polyacrylamide with a molecular weight of 15-25 million.

[0045] As a preferred embodiment of the present invention, the surfactant is BSA-302.

[0046] As a preferred embodiment of the present invention, the water is mineralized water with a mineralization degree of 10000-30000 mg / L.

[0047] The present invention also provides the use of the above-mentioned temperature-resistant gel foam system based on the polymer surface agent in plugging heavy oil reservoirs, characterized in that the core permeability of the heavy oil reservoir is 0.247-0.502 μm 2 .

[0048] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0049] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0050] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0051] The materials and reagents used in the following examples are as follows:

[0052] The polymer is polyacrylamide polymer with a molecular weight of 20 million, purchased from Aixon, France; the surfactant is BSA-302 (Shida Aode Technology Co., Ltd.); sodium dodecyl sulfonate (SLS), sodium dodecylbenzene sulfonate (SDBS), sodium fatty alcohol polyoxyethylene ether sulfate (AES), dodecyl sulfobetaine

[0053] (LHSB), alkylphenol polyoxyethylene ether-10 (OP-10), sodium lignin sulfonate, sodium dodecyl sulfate (SDS), 92%, sodium α-olefin sulfonate (AOS), 94%, China Light Industry Group; cocamidopropyl betaine (CAB-35), 35%, Shandong Yousuo Chemical Technology Co., Ltd.; thiourea, sodium chloride, all analytically pure, high-activity water-soluble phenolic resin (WJ), solid content 75%, Macklin reagent; nitrogen (N2), Beijing Jinggao Gas; zirconium acetate (G501), 75%, Shanghai Macklin; low-activity phenolic resin (DH-1), Shandong Jiushicheng. Other reagents are conventional commercial products.

[0054] Example 1

[0055] A temperature-resistant jelly foam system based on a surfactant polymer is composed of the following components: by mass percentage, 0.3% polyacrylamide polymer, 0.2% surfactant polymer, 0.175% zirconium acetate, 0.6% low-activity phenolic resin, 0.2% sodium dodecyl sulfate, 0.3% thiourea, and the balance is mineralized water with a mineralization degree of 30000 mg / L.

[0056] The molecular weight of the polyacrylamide polymer is 20 million, and the surfactant is BSA-302.

[0057] Example 2

[0058] A temperature-resistant jelly foam system based on a surfactant polymer is composed of the following components: by mass percentage, 0.3% polyacrylamide polymer, 0.2% surfactant polymer, 0.125% zirconium acetate, 0.1% polyethyleneimine, 0.2% sodium dodecyl sulfate, 0.3% thiourea, and the balance is mineralized water with a mineralization degree of 30000 mg / L.

[0059] The molecular weight of the polyacrylamide polymer is 20 million, and the surfactant is BSA-302.

[0060] Example 3

[0061] A temperature-resistant jelly foam system based on a surfactant polymer is composed of the following components: by mass percentage, 0.3% polyacrylamide polymer, 0.2% surfactant polymer, 0.175% zirconium acetate, 0.8% high-activity phenolic resin, 0.2% sodium dodecyl sulfate, 0.3% thiourea, and the balance is mineralized water with a mineralization degree of 30000 mg / L.

[0062] The molecular weight of the polyacrylamide polymer is 20 million, and the surfactant is BSA-302.

[0063] Example 4

[0064] A temperature-resistant jelly foam system based on a surfactant polymer is composed of the following components: by mass percentage, 0.3% polyacrylamide polymer, 0.2% surfactant polymer, 0.175% zirconium acetate, 0.6% low-activity phenolic resin, 0.4% cocamidopropyl betaine, 0.3% thiourea, and the balance is mineralized water with a mineralization degree of 30000 mg / L.

[0065] The molecular weight of the polyacrylamide polymer is 20 million, and the surfactant is BSA-302.

[0066] Example 5

[0067] A temperature-resistant jelly foam system based on a surfactant polymer is composed of the following components: by mass percentage, 0.1% polyacrylamide polymer, 0.3% surfactant polymer, 0.175% zirconium acetate, 0.6% low-activity phenolic resin, 0.4% cocamidopropyl betaine, 0.3% thiourea, and the balance is mineralized water with a mineralization degree of 30000 mg / L.

[0068] The molecular weight of the polyacrylamide polymer is 15 million, and the surfactant is BSA-302.

[0069] Example 6

[0070] A temperature-resistant jelly foam system based on a surfactant polymer is composed of the following components: by mass percentage, 0.5% polyacrylamide polymer, 0.15% surfactant polymer, 0.075% zirconium acetate, 0.4% low-activity phenolic resin, 0.4% cocamidopropyl betaine, 0.3% thiourea, and the balance is mineralized water with a mineralization degree of 45000 mg / L.

[0071] The molecular weight of the polyacrylamide polymer is 25 million, and the surfactant is BSA-302.

[0072] Example 7

[0073] A temperature-resistant jelly foam system based on a surfactant polymer is composed of the following components: by mass percentage, 0.5% polyacrylamide polymer, 0.35% surfactant polymer, 0.225% zirconium acetate, 0.8% low-activity phenolic resin, 0.4% cocamidopropyl betaine, 0.3% thiourea, and the balance is mineralized water with a mineralization degree of 30000 mg / L.

[0074] The molecular weight of the polyacrylamide polymer is 20 million, and the surfactant is BSA-302.

[0075] Example 8

[0076] A temperature-resistant jelly foam system based on a surfactant polymer is composed of the following components: by mass percentage, 0.3% polyacrylamide polymer, 0.2% surfactant polymer, 0.075% zirconium acetate, 0.6% high-activity phenolic resin, 0.2% sodium dodecyl sulfate, 0.3% thiourea, and the balance is mineralized water with a mineralization degree of 30000 mg / L.

[0077] The molecular weight of the polyacrylamide polymer is 20 million, and the surfactant is BSA-302.

[0078] Example 9

[0079] A temperature-resistant jelly foam system based on a surfactant polymer is composed of the following components: by mass percentage, 0.3% polyacrylamide polymer, 0.2% surfactant polymer, 0.225% zirconium acetate, 1.0% high-activity phenolic resin, 0.2% sodium dodecyl sulfate, 0.3% thiourea, and the balance is mineralized water with a mineralization degree of 30000 mg / L.

[0080] The molecular weight of the polyacrylamide polymer is 20 million, and the surfactant is BSA-302.

[0081] Example 10

[0082] A temperature-resistant jelly foam system based on a surfactant polymer is composed of the following components: by mass percentage, 0.3% polyacrylamide polymer, 0.2% surfactant polymer, 0.075% zirconium acetate, 0.05% polyethyleneimine, 0.2% sodium dodecyl sulfate, 0.3% thiourea, and the balance is mineralized water with a mineralization degree of 30000 mg / L.

[0083] The molecular weight of the polyacrylamide polymer is 20 million, and the surfactant is BSA-302.

[0084] Embodiment 11

[0085] A temperature-resistant jelly foam system based on a surfactant polymer is composed of the following components: by mass percentage, 0.3% polyacrylamide polymer, 0.2% surfactant polymer, 0.225% zirconium acetate, 0.2% polyethyleneimine, 0.2% sodium dodecyl sulfate, 0.3% thiourea, and the balance is mineralized water with a mineralization degree of 30000 mg / L.

[0086] The molecular weight of the polyacrylamide polymer is 20 million, and the surfactant is BSA-302.

[0087] Test Example 1

[0088] Different proportions of compound crosslinker I, compound crosslinker II and compound crosslinker III were added to the prepared 0.3wt% polyacrylamide polymer solution, and the balance was mineral water (30000mg / L). The gelation and temperature resistance experiments were carried out at 120℃, the gelation speed of the gel was investigated by the GSC strength code method, and the viscoelasticity of the gel system was measured by the Haake rheometer to investigate its temperature resistance, so as to select the gel system with better temperature resistance and the optimal amount of the crosslinker.

[0089] Depend on Figure 1 It can be seen that with the increase of the amount of cross-linking agent zirconium acetate, the gelling time of the jelly system is shortened thereupon, but the system strength presents a trend of increasing first and then decreasing, this is because zirconium acetate is a metal ion cross-linking agent, has the characteristics of high gelling strength and fast gelling speed, but with the excessive amount of consumption, the cross-linking degree of the system increases, and the polymer molecules are cross-linked into agglomerates to cause the system to dehydrate, thereby causing the strength of the system to decrease. Simultaneously with the increase of the amount of cross-linking agent low-activity phenolic resin, the high temperature stability of the system also presents a trend of increasing first and then decreasing. In order to meet the gelling characteristics of the jelly foam system, it is necessary to meet the requirements that the gelling of the jelly system is rapid, the gelling strength is high and the gelling is stable after the gelling, and it is known that the composite cross-linking agent I has an optimal cross-linking agent ratio and consumption by the influence of two cross-linking agents on the strength of the jelly system.

[0090] Table 1 Gel strength of compound crosslinking agent I

[0091]

[0092] Table 2 Elastic modulus of compound crosslinking agent I after aging at 120℃ for 3 days

[0093]

[0094] From the results in Tables 1 and 2, it can be seen that when the dosage of zirconium acetate is 0.175% and the dosage of low-activity phenolic resin is 0.6%, the system gels quickly and has the best strength, which can reach H, and the elastic modulus can reach 21.94Pa. It is also very stable and not easy to dehydrate.

[0095] Table 3 Gel strength of compound crosslinking agent II

[0096]

[0097] Table 4 Elastic modulus of compound crosslinking agent II after aging at 120℃ for 3 days

[0098]

[0099] From the results in Table 3 and Table 4, it can be seen that when the dosage of zirconium acetate is 0.125 and the dosage of polyethyleneimine is 0.1, the system gelling speed is faster and the strength is optimal. The elastic modulus can reach 16.87Pa, and the stability is strong and it is not easy to dehydrate.

[0100] Table 5 Gel strength of compound crosslinking agent III

[0101]

[0102] Table 6 Elastic modulus of compound crosslinking agent III after aging at 120℃ for 3 days

[0103]

[0104]

[0105] From the results in Tables 5 and 6, it can be seen that when the dosage of zirconium acetate is 0.175 and the dosage of high-activity water-soluble phenolic resin is 0.8., the system gels quickly and has the best strength, which can reach G, and the elastic modulus can reach 20.89Pa. It is also very stable and not easy to dehydrate.

[0106] Test Example 2

[0107] The foaming ability of the foaming agent was determined by the Warning-Blender method. Based on the temperature-resistant gel foam system described in Example 1, different foaming agents and dosages (0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%) were used to prepare 200mL solution, stirred for 2min at 6000r / min, the gas medium was air, and the foam was loaded into a visual reactor. The experimental temperature was 120°C, and the foaming volume and liquid separation half-life of each system were recorded. The foaming agent with better foaming ability and stability was preferred, and its optimal concentration was determined. At the same time, 100mL of different foaming agent solutions of a certain concentration were sealed and placed at 150°C for aging for 24h, taken out and cooled to room temperature, and evaluated by the Waring-Blender method, and compared with the performance of the foaming agent solution without high temperature treatment at the same concentration to investigate the temperature resistance of the foaming agent.

[0108] Depend on Figure 2 It can be observed that the foaming volume of the polymer foam of the nine foaming agents generally increases with the increase of the foaming agent concentration. When the critical concentration is reached, the growth slows down or slightly decreases. Among them, the top five with higher foaming volumes are CAB-35, AOS, SDBS, SDS and AES. The critical concentration of CAB-35 is 0.4wt%, the critical concentration of SDS is 0.2wt%, the critical concentration of SDBS is 0.4wt%, the critical concentration of AOS is 0.3wt%, and the critical concentration of AES is 0.6wt%.

[0109] At the same time by Figure 3 It can be seen that the liquid separation half-life of each system first increases with the increase of the concentration of the nine foaming agents, and then the growth slows down or slightly decreases after reaching the critical concentration. Among them, the foam half-life of SDS, CAB-35 and SDBS at each concentration is significantly higher than that of other systems.

[0110] Figure 4 The results show that CAB-35 has the lowest decrease after high temperature treatment and has the best heat resistance. Among them, SDS has the best foaming ability and foam stabilization ability, but after heating treatment, the comprehensive foam value decreases, but it is still at a high level; OP-10 has the lowest decrease in foam comprehensive value after high temperature treatment, but the comprehensive foam value before and after treatment is the lowest, and the foaming ability and foam stabilization ability are the weakest.

[0111] At the same time, it can be seen from Table 7 that 0.2% of the foaming agent SDS has less effect on the gel strength of the gel system than other foaming agents, and has good compatibility with different compound gel systems. The crosslinking agent I gel system, the crosslinking agent II gel system, and the crosslinking agent III gel system are respectively replaced with different foaming agents described in Table 7 on the basis of Example 1, Example 2, and Example 3.

[0112] Taking into account the foaming ability, foam stabilizing ability and liquid separation half-life of each foaming agent, the foaming agent SDS has excellent foaming ability and foam stabilizing ability, as well as high temperature stability. It can act well on high-temperature oil reservoirs and improve the stability of the foam system. It also has good compatibility with the gel system. Therefore, 0.2% SDS is selected as the foaming agent for the subsequent preparation of gel foam.

[0113] Table 7 Compatibility of different foaming agents with three composite cross-linked gel systems

[0114]

[0115] Test Example 3

[0116] Composite cross-linking system I: by mass percentage, 0.3% polyacrylamide polymer, 0.175% zirconium acetate, 0.6% low-activity phenolic resin, 0.2% sodium dodecyl sulfate, 0.3% thiourea, and the balance is mineralized water with a mineralization degree of 30,000 mg / L.

[0117] Composite cross-linking system II: by mass percentage, 0.3% polyacrylamide polymer, 0.125% zirconium acetate, 0.1% polyethyleneimine, 0.2% sodium dodecyl sulfate, 0.3% thiourea, and the balance is mineralized water, with a mineralization degree of 30,000 mg / L.

[0118] Composite cross-linking system III: by mass percentage, polyacrylamide polymer 0.3%, zirconium acetate 0.175%, high-activity phenolic resin 0.8%, sodium dodecyl sulfate 0.2%, thiourea 0.3%, the balance is mineralized water, and the mineralization degree is 30000 mg / L.

[0119] Use Warning-Blender to generate foam and stir at 6000r / min for 2min. Pour 300mL of foam into a visual reactor and place it in a 150℃ oven. Observe the states of the three jelly-foam systems within 7 days and record the precipitate half-life of each system.

[0120] Depend on Figure 5As shown in Table 8, the foam morphology of three different systems at 1d, 3d, 5d, and 7d, as well as the height of the liquid separation at different aging times, show that the foam morphology of the three composite cross-linked systems is good at 1d, and no obvious liquid separation is observed. When aged for 3d, the foam volume of the composite system II is reduced, the liquid separation is 12mm, and the volume of the single foam in the reactor is large. The foam morphology of the other two systems has no obvious change, among which the liquid separation of the composite system I is 2mm, and the liquid separation of the composite system III is 1mm. When aged for 7 days, the foam volume of the composite system II is less than 50%, and the liquid separation is 50mm. There is a small amount of liquid separation in the other two systems, and the foam volume does not change significantly. With the extension of aging time, the liquid separation amount of each system also increases, among which the liquid separation half-life of the composite system I is 15 days, the liquid separation half-life of the composite system II is 4 days, and the liquid separation half-life of the composite system III is 10 days. From this, it can be judged that the stability of the three jelly systems is in the following order: compound system I>compound system III>compound system II.

[0121] Table 8 Stability analysis of three types of composite cross-linked gel foam systems

[0122]

[0123] Test Example 4

[0124] In order to further improve the stability of the gel foam, a certain amount of a surfactant was added to increase the viscosity of the liquid film of the polymer foam, slow down the liquid separation speed and reduce the amount of liquid separation before the liquid film cross-linked to form a gel, and improve the stability of the polymer solution foam under high temperature conditions. Different amounts of a surfactant were added to the composite cross-linking system I described in Experimental Example 3, and the foam was placed in an oven at 120°C after foaming.

[0125] The relationship between the height of gel foam separation and the viscosity of the liquid film and the amount of the polymerizing agent is as follows: Figure 6-7 As shown. Under the conditions of 120℃ and 30000mg / L NaCl mineralization, when no surfactant was added, the solution viscosity was low, and the gel foam had more precipitate. As the precipitate flowed out, the liquid film of the gel foam became thinner, which was not conducive to the stability of the gel foam. When the amount of surfactant was from 0 to 0.2%, the precipitate in the formation process of the gel foam gradually decreased to zero. When the content of the surfactant was 0.2%-0.3%, the gel foam had no precipitate; when the content of the surfactant was higher than 0.3%, the precipitate amount of the gel foam increased. The main reason is that the surfactant prolongs the precipitate half-life of the foam, allowing the polymer to cross-link with the cross-linking agent for a longer time. Therefore, when the liquid film has a large thickness, cross-linking forms a gel phase liquid film with a higher viscosity, thereby improving the stability of the gel foam and enabling it to be stable for a long time under high temperature conditions; however, too much surfactant will affect the gel strength of the gel due to its amphiphilicity, causing the strength of the gel foam to decrease after forming, which in turn leads to poor stability of the system.

[0126] Test Example 5: Rheological properties test of gel foam

[0127] The viscosity of the water-based foam with a foaming agent concentration of 0.2% SDS (water-based foam component: 0.2% SDS, the balance is mineralized water), the polymer solution foam with a foaming agent concentration of 0.2wt% and a polymer content of 0.3% (polymer solution foam: 0.2% SDS, 0.3% polymer surfactant, the balance is mineralized water), the gel foam system described in Example 1, and the gel foam system of Example 1 and Example 3 after aging at 150°C for 24h were measured using a Haake rheometer at 80°C, 30000mg / L NaCl mineralization, and a shear rate of 7.341 / s. The results are as follows Figure 8-9 At the same time, the elastic modulus and viscous modulus of the gel foam were measured using a Haake rheometer at 80°C, 30000 mg / L NaCl mineralization, 1 Pa stress, and a frequency range of 0.01 to 10 Hz.

[0128] Depend on Figure 8 The results show that the viscosity of the gel foam system described in Example 1 after aging can reach 7000mPa.s, which is 3.5 times that of the unaged system, 7 times that of the polymer foam system, and 40 times that of the water-based foam. The viscosity of the water-based foam and polymer foam systems shows a significant downward trend with the increase of shear time. This is because as the shear time increases, the stability of the water-based foam and polymer foam decreases, and the foam breaks, resulting in a decrease in viscosity. However, the gel foam system has a higher viscosity and a slower change trend in the viscosity, which has good stability. At the same time, Fig. 9 It can be seen from the shear rate change curve that the viscosity of the jelly foam system changes slowly with the increase of shear rate, and the viscosity is relatively large after stabilization, which can be stabilized at 2500mPa.s, indicating that the jelly foam system has excellent shear resistance.

[0129] In summary, through the rheological property tests on different foam systems, it can be seen from the results that the gel foam system has good stability and shear resistance and good rheological properties.

[0130] Test Example 6

[0131] Stability analysis of gel foam system at different temperatures:

[0132] Taking the gel foam system described in Example 1 as an example, while ensuring that other conditions remain unchanged, the temperature is changed to examine the formed gel foam at a temperature of 80-150°C, a 30000 mg / L NaCl mineralization, a system viscosity at 24 hours, and a precipitate volume of the gel foam system after aging for 15 days. The viscosity and precipitate volume of the gel foam change with temperature as shown in FIG. Fig.10 As shown in Figure 2, the volume of the jelly foam changes with temperature. Fig.11 shown.

[0133] Depend on Fig.10 and Fig.11 It can be seen that the stability of the gel foam is between 80 and 150 °C, and the gel foam system can exist stably in a high temperature environment. When the temperature rises to 110 °C, a stable gel foam can be formed. At this time, the gel foam does not undergo liquid precipitation, and the half-life is extended to 16 days. When the temperature is 120 °C, its liquid precipitation half-life is 15 days. With the increase of aging time, the liquid precipitation height of the gel foam also increases. The liquid precipitation height increases to 30 mm after aging for 15 days, and the foam volume retention rate is 70%. When the temperature rises to 150 °C, its liquid precipitation half-life can still reach 5 days, indicating that the gel foam system has excellent high-temperature stability and a long action time under high-temperature reservoir conditions, thereby playing a lasting plugging and profile control role.

[0134] Test Example 7

[0135] Stability analysis of gel foam system under different mineralization degrees

[0136] Based on the temperature-resistant jelly foam system described in Example 1, the stability changes of the high-strength jelly foam system at different NaCl concentrations were investigated. Fig.12 and Fig.13 It can be seen that for the jelly foam system, the amount of liquid precipitation increases with the increase of NaCl concentration, and the viscosity decreases with the increase of NaCl concentration, indicating that the increase of NaCl content is not conducive to the stability of the jelly foam. This is because sodium ions can compress the thickness of the diffusion layer, increase the curling degree of the molecules, and reduce the viscosity of the polymer solution, thereby affecting the foam stabilization effect of the polymer. In addition, when the salt concentration is too high, the ionic surfactant is easily salted out and precipitated in the solution, which also has a certain negative impact on the foam stability. With the increase of salt concentration, the viscosity generally changes, but the viscosity of the jelly foam system is still at its normal level when the NaCl concentration is 30000-45000 mg / L.

[0137] Test Example 8

[0138] The water-based foam, polymer solution foam and the gel foam described in Example 5 (water-based foam component: 0.2% SDS, the balance is mineral water; polymer solution foam: 0.2% SDS, 0.3% surfactant, the balance is mineral water) were observed by optical microscopy.

[0139] The morphology was observed after magnification 100 times and photographed. In order to compare the microstructures of water-based foam, polymer solution foam and gel foam and analyze their temperature resistance mechanism, a 200F scanning electron microscope was used to take photographs of the water-based foam, polymer solution foam and gel foam after freeze-drying.

[0140] Fig.14 As shown, in the water-based foam and polymer foam state, the liquid separation speed of the foam outer wall is relatively fast, the foam wall quickly becomes very thin, the volume of a single foam expands, and the foam shape changes from round to polygonal, and is on the verge of bursting; the gel foam described in Example 5 has a larger foam structure after aging, and the outer wall forms a gel phase and becomes thicker. The thicker gel liquid film makes the foam structure more stable under high temperature conditions and not easy to burst.

[0141] Fig.15 As shown, under a 1000x cryo-scanning electron microscope, after the water-based foam is freeze-dried and the water is removed, only the entangled long chains of the foaming agent and the NaCl crystal structure are left; the pore structure of the foam can be observed in the polymer foam after the water is lost, and it can be seen that the pore structure of the foam is composed of long polymer chains; the gel foam described in Example 5 loses water after freeze-drying, and after a magnification of 1000 times, it can be observed that the liquid film of the gel foam forms a dense network-like gel structure with good stability.

[0142] Test Example 9 Study on the plugging performance of gel foam system

[0143] The plugging ability of the gel foam system on cores with different permeabilities was investigated. The experimental method was as follows: at a temperature of 150°C, a back pressure of 10 MPa, and a fixed injection gas-liquid ratio of 3:1, the gel foam system was injected into cores with permeabilities of 0.5, 1.0, and 2.0 μm at a rate of 1.2 mL / min. 2 The jelly foam system described in Example 1 was injected into the core of PV to investigate the plugging performance of the jelly foam. The experiment mainly investigated the pressure difference of the water-driven core before and after the injection of the jelly foam, and the plugging rate of the system was calculated based on this. The plugging effect of the core with different permeability is shown in Table 9 and Fig.17 The experimental setup is shown in Fig.16 shown.

[0144] As shown in Table 9 and Fig.17 As shown in the figure, the gel foam system has different plugging capabilities for cores of different permeabilities, showing the selective plugging characteristics of plugging high permeability cores but not low permeability cores. 2When the system is difficult to inject, the core cannot be plugged; when the permeability is 0.247-0.502μm 2 When the core permeability increases, the plugging ability of the system to the core first increases and then decreases slightly; when the core permeability is 0.502μm 2 The plugging rate is 99.59%, with excellent plugging performance. At the same time, after injecting the gel foam for plugging, the equilibrium pressure difference after the secondary water flooding 7PV is stable at 4987.6kPa, indicating that the gel foam has strong anti-scouring performance and excellent stability.

[0145] Table 9 Gel foam plugging performance under different matrix permeability

[0146]

[0147]

[0148] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A temperature-resistant jelly foam system based on a surfactant, characterized in that: The invention comprises the following components: by mass percentage, 0.1% to 5% of polymer, 0.15% to 0.35% of surfactant, 0.1% to 1.0% of cross-linking agent, 0.1% to 0.6% of foaming agent, 0.1% to 0.5% of deoxidizer, and the balance is water.

2. The temperature-resistant jelly foam system based on the surfactant according to claim 1, characterized in that: The cross-linking agent consists of zirconium acetate and low-activity phenolic resin. In the system, the mass percentage of zirconium acetate is 0.075%-0.225%, and the mass percentage of low-activity phenolic resin is 0.4%-0.8%.

3. The temperature-resistant jelly foam system based on the surfactant according to claim 1, characterized in that: The cross-linking agent consists of zirconium acetate and polyethyleneimine. In the system, the mass percentage of zirconium acetate is 0.075%-0.225%, and the mass percentage of polyethyleneimine is 0.05%-0.2%.

4. The temperature-resistant jelly foam system based on the surfactant according to claim 1, characterized in that: The cross-linking agent consists of zirconium acetate and high-activity phenolic resin. In the system, the mass percentage of zirconium acetate is 0.075%-0.225%, and the mass percentage of high-activity phenolic resin is 0.6%-1.0%.

5. The temperature-resistant jelly foam system based on the surfactant according to claim 1, characterized in that: The foaming agent is any one of sodium lauryl sulfate, cocamidopropyl betaine, and sodium α-olefin sulfonate.

6. The temperature-resistant jelly foam system based on the surfactant according to claim 1, characterized in that: The deoxidizer is thiourea.

7. The temperature-resistant jelly foam system based on a surfactant according to claim 1, characterized in that: The polymer is polyacrylamide with a molecular weight of 15-25 million.

8. The temperature-resistant jelly foam system based on a surfactant according to claim 1, characterized in that: The surfactant is BSA-302.

9. The temperature-resistant jelly foam system based on a surfactant according to claim 1, characterized in that: The water is mineralized water with a mineralization degree of 10000-30000 mg / L.

10. The use of the temperature-resistant gel foam system based on the polymerizing agent according to any one of claims 1 to 9 in the production process of high-temperature heterogeneous oil layers with steam stimulation, characterized in that: The core permeability of the oil layer is 0.247-0.502 μm 2 .

Citation Information

Patent Citations

  • Chemical secondary-crosslinking jelly foam water plugging and profile controlling liquid

    CN102604606B

  • Temperature-resistant and salt-resistant gel foam containing phosphonic acid structure, and preparation method and application thereof

    CN110982502A

  • A high-temperature and high-salt resistant reinforced foam plugging agent and its reservoir injection method

    CN113201318B

  • Temperature-resistant foam gel as well as preparation method and application thereof

    CN110846012A

  • Bottom water reservoir multi-slug plugging agent and plugging method thereof

    CN111334268A